2017
DOI: 10.1038/jp.2017.54
|View full text |Cite
|
Sign up to set email alerts
|

Factors leading to rehospitalization for tracheostomized and ventilator-dependent infants through 2 years of age

Abstract: The risk for rehospitalization for infants requiring tracheostomy and ventilator support was affected by prolonged oxygen use, prolonged ventilator dependence, inhaled steroid use and equipment malfunction, and was equally distributed throughout the first 2 years of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 20 publications
5
36
0
Order By: Relevance
“…In our previous study, we reported that oxygen and diuretic use in infants with BPD increased around 1 year of age and then gradually decreased by 2 years of age. 6 In this study, we found a similar trend for gastrointestinal and renal medications; however, cardiac medications, endocrine medications, neurologic medications, and inhaled corticosteroids did not decrease significantly over the 3-year period. A probable reason for this difference could be the weaning of diuretics for severe BPD patients.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In our previous study, we reported that oxygen and diuretic use in infants with BPD increased around 1 year of age and then gradually decreased by 2 years of age. 6 In this study, we found a similar trend for gastrointestinal and renal medications; however, cardiac medications, endocrine medications, neurologic medications, and inhaled corticosteroids did not decrease significantly over the 3-year period. A probable reason for this difference could be the weaning of diuretics for severe BPD patients.…”
Section: Discussionsupporting
confidence: 61%
“… 3 5 Prior studies indicate that rehospitalization, equipment malfunction, and tracheostomy at <1 year of age are significant risk factors for mortality. 1 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…3-5 CWT are a growing population as pediatric medical advances result in increased survival of children with critical airways and chronic respiratory failure. 6-9 CWT were previously thought to be too complex to be cared for at home and were hospitalized for long periods. 10 Now increasing recognition supports that CWT can be successfully cared for at home with proper social, economic, and medical supports.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The combination of significant medical complexity, potential for life-threatening complications, 22 and lack of standardization of care transitions and training for caregivers/home nursing agencies place CWT at high risk for morbidity and mortality fostering dependence on crisis-driven care. 6,9,23,24 CWT have high hospital readmission rates particularly following discharge after initial tracheostomy placement with rates varying from 20% to 50% in the first 3 months. 8,[25][26][27] High readmission rates contribute to already elevated levels of caregiver burden and increased health care costs, 19,24,28,29 and are costly and stressful for patients/families.…”
mentioning
confidence: 99%
“…This lower rate of RSV infection may have been due to strict compliance with Synagis administration in tracheostomized and ventilator-dependent infant's medical home clinic where NICU physicians were the primary pediatricians for this cohort of infants. 16 Interestingly, there were no deaths reported after discharge from the NICU in the severe BPD cohort for this study. This finding was also noted in a BPD study done from 2010 to 2013 17 where there were seven deaths reported post NICU discharge but only in the mild/ moderate BPD groups.…”
Section: Discussionmentioning
confidence: 74%